Identifikasi Zat Pewarna Rhodamin B Pada Terasi Yang Diperjualbelikan Di Pasar Toddopuli Kota Makassar - Latifatul Mutmainnah; Hasan Lampe; Fitrah Sari Fitrah Sari (Prodi D-III Analis Kesehatan niversitas Indonesia Timur, 2017)
Research has been carried out on the identification of Rhodamin B dyes in the traded terasi at Toddopuli Market, Makassar. The background of this research is that the shrimp paste traded in the Toddopuli market in Makassar may contain Rhodamin B coloring agents, but in fact in the field it shows that almost all unbranded shrimp paste sold in the market are all red and have a rough texture unlike most shrimp paste. Where the community as consumers do not know the impact that will be caused and the danger of Rhodamin B coloring agents for health. This research was conducted to identify the presence of Rhodamin B coloring agent found in the shrimp paste. This type of research is a qualitative research laboratory research that is to describe dyes in shrimp paste using the purposive sampling technique using 5 samples and the method used is Thin Layer Chromatography. From the results of this study, the five tested samples gave positive reactions to Rhodamin B. Therefore, consumers should be careful and more aware of consuming food so that it does not adversely affect health.